METHODS OF USING "FSMU" TECHNOLOGY DURING LABORATORY TRAINING - Soliyeva Madina Murodjon qizi (Journals Park Publishing, 2024)
The article is devoted to the implementation of innovative educational technologies. Including methods of using the "Thought, reason, example, generalization (FSMU)" method in various parts of laboratory classes in physics at MIA academic lyceums, and analysis of the possibilities for students to draw conclusions from a general idea, acquire knowledge, skills, and abilities with the help of this method done.
Keywords: FSMU method, educational technologies, problem situation, debate, opinion.